PERANCANGAN MESIN PEMERAS LENDIR BIJI KAKAO (DEPULPER) TIPE ROTARY UNTUK MENINGKATKAN MUTU BIJI BUAH KAKAO DESA SUMBERAGUNG KABUPATEN BANYUWANGI - Nuraini Lusi; Afandi Akhmad; Catrawedarma IGNB; Anam Chairul (ROTOR, 2017)
The purpose of this activity is to improve the productivity of the farmers in the success of cocoa fruit through the use of appropriate technology for the separation of coco seeds / squeezer machine, with the application of this technology is expected to assist farmers in the production process so that the quality results of cocoa produced will be more optimal. Cocoa bean separator machine serves to accelerate the process of separation of salut which during this process is still manually and takes a long time. This salute separator machine as much as possible the process is easy and the results are really on target. The main objective of making cocoa depulper is to assist cocoa farmers in the process of harvesting and improving the quality of crops so that the needs of cocoa farmers can be fulfilled. Keywords: cocoa, salute, depulper, rotary system